Diffusion globale et fonctionnements locaux : géographies des scènes metal - Laurent Beauguitte; Hugues Pécout (M@ppemonde)
This article focuses on the emergence and worldwide distribution of a musical genre that appeared in the late 1960s: heavy metal. Using the metal-archives database with over 120,000 groups, we illustrate the spatial diffusion of the phenomenon while highlighting the countries most affected by the phenomenon, considering the number of groups and the rate of groups per 10,000 inhabitants. With the rise in popularity of this genre, a multitude of sub-genres has appeared and the second part of the article highlights national specificities. Finally, the third part focuses on how two local scenes, Argentina and Russia, function with a mixture of musical and political affinities. In order to ensure both the reproducibility of the research and the examination of other research questions, all data and R-scripts are provided under an open license.